A Qualitative Approach to Develop Niche Social Networks A Reading Social Networks Case Study - Pontes Miranda, James William [UNESP]; Rodrigues Bueno, Danilo Henrique [UNESP]; Gratao de Souza, Rogeria Cristiane [UNESP]; Valencio, Carlos Roberto [UNESP]; Hammoudi, S.; Maciaszek, L.; Missikoff, M. M.; Camp, O.; Cordeiro, J. (Scitepress, 2016)
The daily use of social networks is in growth around the world and this includes niche social networks, which have as a main feature an audience segmented by some kind of affinity that particularizes a group. This paper focuses on a specific type of niche social network, which are the reading social networks, aiming to perform a qualitative analysis of this type of website The goal is to understand how the qualitative factors can affect the users and also to serve as reference for the construction of new niche social networks, based on quality factors widely used for the creation of various types of software systems. Thus, this paper aims to fill a need for specific studies of niche social networks and also the influence of qualitative factors of software in websites, helping users and developers of reading social networks.
Keywords: Social Networks; Software Quality Assurance; Web